SUBCORTICAL DYSARTHRIA: CLINICAL DESCRIPTION - Iminjonova Mokhichehra Alimardon qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article provides a scientific analysis of the clinical characteristics of subcortical dysarthria, its pathophysiological mechanisms, and speech disorders resulting from lesions of the central nervous system at the level of the basal nuclei. Hyperkinesias, changes in muscle tone, incoordination of articulatory movements, disorders of timbre and intonation, as well as instability of speech rhythm, characteristic of subcortical dysarthria, are described as clinical signs. Speech manifestations of subcortical dysarthria typical of dystonic, athetoid, and hemiballistic forms, changes in the phonation process, and logopedic-diagnostic criteria are also analyzed on a theoretical basis. The article provides scientific information on the neurological basis of this type of dysarthria, its impact on speech motor skills, and the scientific methods of providing corrective and pedagogical assistance.